IMPLEMENTATION OF HOUSEKEEPING DEPARTMEN DUTY IN CLEANING THE BATHROOM AT KTM RESORT BATAM KEPULAUAN RIAU - ", Safarwatunnisak; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aims to determine about the implementation of housekeeping department duty in cleaning bathroom at KTM Resort Batam Kepulauan Riau.KTM Resort originally derived from the name of the hotel owner itself is MR "KOH TIET MING", which was built in 2002. However on 07 september 2017 KTM name no longer use the name of MR KOH TIET MING again but "KNOWLEDGE TEAM MINDFULL" above the work team. At first KTM Resort is a seafood restaurant called Revenea restaurant which is currently called karang restaurant and has an inn named ROISTONEA which is currently a family villa. KTM has the full name of PT HOTEL KTM INDONESIA but generally local and non local people know it by the name of KTM RESORT, KTM Resort. KTM Resort Batam Hotel located on the road Colonel Sugiono, Tgpinggir sekupang - Batam.This research to make use qualitative method to analysis set of case, wich to become the key informan in this research as much as 4 people’s. that is 1 housekeeping supervisor and 3 housekeeping roomboy/room maid. sources were obtained through observation, interview, and documentation. Based on result of this research, the conlusions of this research are implementation of housekeeping department duty in cleaning bathroom has been done, but still need raising required.keywords :Implementation, Housekeeping, Hotel